Algebraic Combinatorics 2018
DOI: 10.5802/alco.2
|View full text |Cite
|
Sign up to set email alerts
|

Lower bound cluster algebras: presentations, Cohen–Macaulayness, and normality

Abstract: We give an explicit presentation for each lower bound cluster algebra. Using this presentation, we show that each lower bound algebra Gröbner degenerates to the Stanley-Reisner scheme of a vertexdecomposable ball or sphere, and is thus Cohen-Macaulay. Finally, we use Stanley-Reisner combinatorics and a result of Knutson-Lam-Speyer to show that all lower bound algebras are normal.A more interesting and morally correct statement is that each of these spaces possesses a stratification such that each stratum natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…We would like to remark that this paper is not the first to make a connection between cluster algebras and Gröbner theory. In [41] Muller, Rajchgot and Zykoski obtained presentations for lower bounds of cluster algebras using Gröbner theory. Further, it is worth noticing that the theory of universal coefficients for cluster algebras is particularly well-developed for finite and surface type cluster algebras, see [44].…”
Section: Spec(r C (A))mentioning
confidence: 99%
“…We would like to remark that this paper is not the first to make a connection between cluster algebras and Gröbner theory. In [41] Muller, Rajchgot and Zykoski obtained presentations for lower bounds of cluster algebras using Gröbner theory. Further, it is worth noticing that the theory of universal coefficients for cluster algebras is particularly well-developed for finite and surface type cluster algebras, see [44].…”
Section: Spec(r C (A))mentioning
confidence: 99%
“…, 𝑦 𝑛 ] and ideal 𝐾 𝑄 ⊆ 𝑅 𝑄 such that the lower bound algebra L 𝑄 associated to Q can be expressed as L 𝑄 = 𝑅 𝑄 /𝐾 𝑄 . Fix the lexicographical monomial order with [32,Theorem 1.7] and the proof of [32,Theorem 3.3], in < 𝐾 𝑄 is the Stanley-Reisner ideal of a simplicial complex Δ on the vertex set {𝑦 1 , . .…”
Section: Graded Lower Bound Cluster Algebrasmentioning
confidence: 99%
“…Remark 5.4. It follows from [32,Theorem 1.7] that 𝐾 𝑄 is homogeneous if and only if Q has no frozen vertices and Q has exactly two arrows entering each vertex and two arrows exiting each vertex.…”
Section: Graded Lower Bound Cluster Algebrasmentioning
confidence: 99%
“…In [BMRS15], Benito, Muller, Rajchgot, and Smith proved that locally acyclic cluster algebras are strongly F-regular (when defined over a field of prime characteristic) and that they have at worst canonical singularities (over a field of characteristic 0). Further, Muller, Rajchgot, and Zykoski [MRZ18] showed that the lower bound cluster algebra (which is an approximation of a given cluster algebra obtained by a suitable truncation of the construction process) is Cohen-Macaulay and normal.…”
Section: Introductionmentioning
confidence: 99%